Prophylactic tranexamic acid to reduce blood loss and related morbidities during hysterectomy: a systematic review and meta-analysis of randomized controlled trials - Ahmed Abu-Zaid; Saeed Baradwan; Ehab Badghish; Rayan AlSghan; Ahmed Ghazi; Bayan Albouq; Khalid Khadawardi; Nora F AlNaim; Latifa F AlNaim; Meshael Fodaneel; Fatimah Shakir AbuAlsaud; Mohammed Ziad Jamjoom; et al. (Korean Society of Obstetrics and Gynecology, 2022)
To perform a systematic review and meta-analysis of all randomized controlled trials (RCTs) that evaluated the efficacy and safety of prophylactic tranexamic acid (TXA) versus a control (placebo or no treatment) during hysterectomy for benign conditions. Six databases were screened from inception to January 23, 2022. Eligible studies were assessed for risk of bias. Outcomes were summarized as weighted mean differences and risk ratios with 95% confidence intervals in a random-effects model. Five studies, comprising six arms and 911 patients were included in the study. Two and three studies had an overall unclear and low risk of bias, respectively. Estimated intraoperative blood loss, requirement for postoperative blood transfusion, and requirement for intraoperative topical hemostatic agents were significantly reduced in a prophylactic TXA group when compared with a control group. Moreover, postoperative hemoglobin level was significantly higher in the prophylactic TXA group than in the control group. Conversely, the frequency of self-limiting nausea and vomiting was significantly higher in the prophylactic TXA group than in the control group. There were no significant differences between the groups in terms of surgery duration, hospital stay, and diarrhea rate. All the RCTs reported no incidence of major adverse events in either group, such as mortality, thromboembolic events, visual disturbances, or seizures. There was no publication bias for any outcome, and leave-one-out sensitivity analyses demonstrated stability of the findings. Among patients who underwent hysterectomy for benign conditions, prophylactic TXA appeared largely safe and correlated with substantial reductions in estimated intraoperative blood loss and related morbidities.